PEMANFAATAN MEDIA SOSIAL SEBAGAI STRATEGI PROMOSI WISATA AIR TERJUN DI DESA SANTONG, KECAMATAN KAYANGAN KABUPATEN LOMBOK UTARA: PEMANFAATAN MEDIA SOSIAL SEBAGAI STRATEGI PROMOSI WISATA AIR TERJUN - Wafiq Laelatul Kodrianingsih; Maiser Syaputra; Pande Komang Suparyana; Andi Tri Lestari; Indra Wahyu; Baiq Mega Kurnia; Yuni Fatmala; Imro’atul Hapizah; Mei Sukmawati; Shela Hadri Dhuha; Marwati Maryam Shabrina; Ferdian Arya Kusuma; M. Nizar Hamdani; Lalu Anugrah Wira Anggardikzza (Universitas Mataram, 2023)
Kuliah Kerja Nyata (KKN) is a form of community service activity carried out by tertiary institutions. This KKN activity was carried out in Santong village, which is located in Kayangan sub-district, North Lombok district. Santong village is known as the kingdom of waterfall because in this area there are more than 30 types of waterfalls which are local and international tourist destinations. One of the famous waterfalls is Tiu Teja, Tiu Sekeper, and Tiu Prabu waterfalls. However, since the earthquake that hit Lombok in 2018 and not to mention the Covid-19 pandemic which has added to the lack of visitors so that waterfall tourism in Santong village seems to be in suspended animation. There are several methods of activity carried out, namely by (1) creating a tourism website, (2) updating the gate to waterfall tourism, (3) making disaster mitigation instructions or signs at waterfall tourism, and (4) procuring trash bins. This KKN is being held from December 2022 to February 2023 which aims to revive waterfall tourism with a promotional strategy through social media. The result of this activity is the availability of a special website containing tourism data in Santong village so that it can increase existence and increase the number of tourists so that it can improve the economy of the village community. In addition, the KKN group is also involved in various activities such as TPQ competitions in Santong village, posyandu and PKK activities, mutual cooperation, teaching the Koran, village competitions, and routine recitations for each hamlet. From the several activities that have been carried out, this KKN activity is able to answer some of the problems that exist in Santong village related to the development of tourism potential and the existing potentials in the fields of education, health, and others.